Temperature allocation in composite bridge box girder segment under the effect of summer Iraqi environmental load (Eurasian Journal of Engineering and Technology, 2023)
The bridge is constructed in an open environment, exposing every part of the bridge to environmental load. This paper studies the impact of the Bagdad environmental load that involves wind speed, air temperature, and solar radiation on the composite bridge box girder segment. These environmental loads are variable hourly, leading to nonlinear temperature distribution inside the segment. This nonlinear temperature distribution inside the segment led to generating thermal stress inside the segment. This paper reveals the magnitude and allocation of thermal stress inside the segment. Furthermore, this paper provides the numerical result for thermal stress inside the segment by using a unique simulation in the COMSOL program to calculate the effect of these environmental loads on the temperature allocation inside the segment